Acetylcholinesterase inhibitory activity of Ocotea pomaderroides extracts: HPLC-MS/MS characterization and molecular modeling studies. Issue 4 (16th February 2022) - Reis, Isabella M. A.; Cassiano, Dayse S. A.; Conceição, Rodrigo S.; Freitas, Humberto F. de; Pita, Samuel S. da R.; David, Jorge M.; Branco, Alexsandro
Abstract: The present work describes the acetylcholinesterase inhibitory activity of Ocotea pomaderroides extracts besides the chemical composition of chromatographic fractions. The hexane, dichloromethane and ethyl acetate extract soluble fractions showed high Electrophorus electricus acetylcholinesterase ( Eel AChE) inhibition (92.18, 71.86 and 74.25%, respectively) while the butanolic and aqueous extracts showed moderate to low activities (44.48 and 20.74%, respectively). The high-performance liquid chromatography coupled with electrospray ionization multiple-stage mass spectrometry (HPLC-ESI-MS n ) analysis led to the identification of the alkaloids and flavonol glycoside derivatives present in these extracts. The binding profile of the alkaloids and their atomic effect on 3D structure of Electrophorus electricus AchE (EelAChE) were assessed with molecular modeling. Graphical Abstract: